Efektivitas diskon dan promosi digital dalam mempengaruhi keputusan pembelian konsumen wanita di e-commerce Indonesia - Sari, Maya Desvita; Chaniago, Harmon; Indira, Hidya (Nur Science Institute, 2025)
The objective of this study is to examine the impact of discounts and digital promotions on consumer purchase decisions on the largest e-commerce platforms in Indonesia, specifically Shopee, Tokopedia, and Lazada, with a focus on female consumers in the city of Bandung. The background of this research is driven by the rapid growth of e-commerce and the high level of competition among platforms, which encourages the use of discount and digital promotion strategies to attract consumer attention. A survey method is employed in this study, utilising a quantitative approach and a purposive sampling technique, with 254 female respondents aged 18–34 years. Data was analysed using measurement models and structural models with the Partial Least Squares (PLS) approach. The results indicate that discounts and digital promotions have a positive and significant impact on consumer purchasing decisions, with discounts having a greater influence than digital promotions. These findings underscore the importance of developing targeted marketing strategies that incorporate discounts and digital promotions to effectively influence purchase decisions. This study concludes that optimal use of promotional strategies can enhance the competitiveness of e-commerce platforms in the increasingly competitive digital market.